A variant of GRK5 is associated with the therapeutic efficacy of repaglinide in Chinese Han patients with type 2 diabetes mellitus. Issue 3 (16th April 2018) - Shang, Zhenhai; Han, Feifei; Zhou, Xueyan; Bao, Zejun; Zhu, Jing; Wang, Tao; Lu, Qian; Du, Lei; Li, Wei; Lv, Dongmei; Yin, Xiaoxing
Abstract: Post‐Market Research We aimed to investigate the impact of G protein‐coupled receptor kinase 5 ( GRK5 ) rs10886471 polymorphism on repaglinide efficacy in Chinese patients with type 2 diabetes mellitus (T2DM). A total of 300 T2DM patients and 210 healthy controls were genotyped for GRK5 rs10886471 on a three‐dimensional polyacrylamide gel‐based DNA microarray. Eighty‐five patients with the same genotypes of cytochrome P450 (CYP) 2C8*3 139Arg and organic anion‐transporting polypeptide 1B1 (OATP1B1) 521TT were randomly selected to orally take repaglinide for eight consecutive weeks. Then, the biochemical indicators and pharmacodynamic parameters were measured before and after repaglinide treatment. The T allelic frequency of GRK5 rs10886471 was higher in T2DM patients than in healthy subjects ( p < .01). T2DM patients with genotypes CC and CT at GRK5 rs10886471 had a significant reduction in terms of fasting plasma glucose (FPG) compared with those with genotype TT ( p < .01). In addition, the carriers of genotypes CC and CT at GRK5 rs10886471 had higher differential values of postprandial serum insulin (PINS) compared with genotype TT carriers ( p < .05). These findings suggest that GRK5 rs10886471 polymorphism may influence the therapeutic efficacy of repaglinide in Chinese Han T2DM patients.